Mosque a place for Moslems - Mangarun, Cairia P.; Florendo, Raquel Baltazar (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Mosques -- Philippines; Islamic architecture -- Philippines